Pharmaceutical Analysis of a Novel Propargyl-linked Antifolate Antibiotic in the Mouse - Hoody, John (J Chromatogr B Analyt Technol Biomed Life Sci, 2017)
Antimicrobial resistance to current antibiotics is a significant public health problem and the need for new antibiotics is a compelling one. We have been developing a new series of antibiotics, propargyl-linked diaminopyrimidines, based on the structure of trimethoprim. To date we have discovered compounds that are effective inhibitors of dihydrofolate reductase (the target of trimethoprim), that are potent antibiotics in vitro against a range of Gram-positive pathogens including methicillin-resistant S. aureus, and that are non-toxic in mammalian cell culture. In this study we report the development of an LC-MS-based protocol for the quantification of our lead antibiotic 37D1-UCP1099 and the application of this assay to follow the concentration of the compound in mouse plasma after intraperitoneal administration. Extraction of 37D1-UCP1099 from mouse plasma was achieved through a liquid-liquid extraction with ethyl acetate. Separation was performed utilizing a reverse-phase C18 column with a ten minute isocratic elution using 47:53 (v/v) 10 mM NH(4)HCO(3):acetonitrile. The lower limit of quantitation for 37D1-UCP1099 was 50 ng.mL(−1) and the assay showed a dynamic range of 50–4000 ng.mL(−1) with good linearity (r(2) ≥ 0.996 for all fits). Intra-day and inter-day precision and accuracy were within 11.3% (%RSD) and 6.6% (%RE) respectably. We have demonstrated that the compound is stable under the assay procedures. The compound was shown to have a mean residence time of 26.2 ± 1.0 min and a half-life of 18.2 ± 0.7 min after intraperitoneal delivery at 5 mg.kg(−1). These studies now form the foundation of our work to develop additional analogs of 37D1-UCP1099 with improved pharmacokinetic properties.